Continuity & relevance of Malay traditional performance art in this millennium - Rahmah, B. (University of Malaya, 2005)
Though it is common knowledge that creativity is the creator's own, the product is also the sum of a creative process encompassing the thoughts, emotions, and experience of its time. In time it becomes the signifier and statement of its importance and values for that time frame. By then, together with other art forms, it would serve to express the aesthetic leanings of the time. The resilience of an art form is not only reflected in its life span, but also in the acceptance and recognition of the public at large. This also means that an art form must reach a certain maturity through the test of time and civilization before it can be regarded as an art heritage to be treasured by the nation inheriting it. With art artifacts falling within the mold of fine and visual arts, this recognition is more readily prescribed as compared to the more elusive performance art. However, with the advance of technological knowledge, both visual and performance art can now be recorded, improved, and innovated upon, and although this technological knowledge can be at the expense of the artistic originality, it has contributed greatly to the posterity of art forms and its artistic endeavors. Structural and socio-cultural studies of traditional performance art has also enhanced its further discussion, and led to its enforcement and significance as a social phenomenon. Perhaps Christopher Norris can help us sum up the societal significance of traditional performances, or any performances for that matter, when he said, "Structuralism in all cultural systems could be studied from a 'synchronic' viewpoint which would bring out their various related levels of signifying activity." (Christopher Norris, 2003).